Hydrodeoxygenation of lignin model compounds to alkanes over Pd–Ni/HZSM-5 catalysts. Issue 3 (June 2020) - Zhao, Yun-Peng; Wu, Fa-Peng; Song, Qing-Lu; Fan, Xing; Jin, Li-Jun; Wang, Rui-Yu; Cao, Jing-Pei; Wei, Xian-Yong
Abstract: In this work, a bimetallic catalyst of Pd and Ni supported on HZSM-5 was designed and evaluated in the hydrodeoxygenation of model compounds representing various C–O bonds in lignin. The effects of temperature, holding time, and initial H2 pressure on the catalytic performance of the Pd–Ni/HZSM-5 catalyst were investigated. The results indicated that the Pd–Ni/HZSM-5 catalyst exhibited superior catalytic activity towards the conversion of the model compounds to alkanes compared to its monometallic counterparts. Direct cleavage of the C–O bond in DPE was achieved under low H2 pressure, mainly producing benzene and minor amounts of phenol and cyclohexane, while at high H2 pressure, the reaction pathway was altered towards hydrogenation of the benzene ring, followed by then cleavage of the C–O bond to afford only cyclohexane. Moreover, the Pd–Ni/HZSM-5 catalyst showed high activities when applying other substrates including anisole, veratrole, guaiacol, benzyloxybenzene, phenethyl phenyl ether, and dibenzyl ether. Graphical abstract: Image 1 Highlights: Pd–Ni/HZSM-5 is an effective catalyst for the hydrodeoxygenation of C–O bond in lignin model compounds. Initial H2 pressure plays an important role in the hydrodeoxygenation of diphenyl ether. The synergetic effects between bimetallic metals and HZSM-5 enhanced the catalytic activity.